Sustentabilidad desde abajo. - Chan, Jennifer (CLACSO, 2017)
What does it mean to research sustainability from a gender perspective? This volume stems from the interest of a group of academics in approaching this question and encouraging academic discussion on the relationship between gender and sustainability. The articles that make up this book shed light on how gender relations with sustainability are intersected by other categories. This forces us to rethink sustainability beyond its definitions "from above" and more in the way in which different actors answer their definitions from struggles "from below" through different strategies marked by gender, class and ethnicity.